Analyse des erreurs d’écriture et des efforts des élève de classe XI SMA Negeri 1 Demak en étudiant le français - Budiyanti, Elis; Vitri Widayanti, Diah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
Writing skills are one of the skills that must be mastered in learning French to communicate with the 321 million people in the world who use the language. Errors in writing are unavoidable due to differences in language systems. Therefore, this study aims to describe 1) the types of mistakes made by students, 2) student responses to work corrections, and 3) students’ efforts in overcoming writing errors. This study is a descriptive qualitative study that has a sample of 51 students of SMA Negeri 1 Demak by analysing the student work results using data collection from student work results, by analysing mistakes, describing mistakes, explaining mistakes by providing feedback about mistakes made, and questionnaires about mistakes made and their ways or efforts. To correct such a mistake, use data cards and recapitulation tables to analyse the data. The results showed 1) writing mistakes in grammatical elements were most commonly found, namely 106 grammatical mistakes, and 45 orthographic errors. 2) The students’ response to the corrections given is responded well, namely with the idea of correcting the results of the assignments given can help find out the location of errors and justifications for writing in French and 3) the effort made by students in learning French in Writing Skills, namely students argue by learning, looking for information, correcting writing errors, paying more attention to learning and not hesitating to ask questions during learning.